Model-free Current Predictive Control of Open-winding Permanent Magnet Synchronous Motor - Lu, Bing; Deng, Fujun (International Journal of Mechanical and Electrical Engineering, 2024)
Aiming at the problem that the traditional model current predictive control of open-winding permanent magnet synchronous motor with common bus is easy to change its motor parameters, the current predictive control and model-free control are combined. On this basis, a linear state observer is added to estimate the system disturbance and solve the time-consuming and complicated problem of model-free control disturbance. The improved model-free current predictive control selects the best basic voltage vector and action time through the value function and voltage vector sector. The zero-sequence voltage to be compensated is obtained by the difference between the zero-sequence voltage generated by non-zero vector and the reference zero-sequence voltage, and the mixed zero vector injected and the action time are selected and calculated, so that the system can achieve optimal compensation. Finally, Matlab/Simulink is used for simulation, which verifies the effectiveness and feasibility of the experiment.